Appendicitis and appendectomy: a retrospective survey in South Indian population. - Naveen, K; Sareesh, NN; Satheesha, BN; Murlimanju, BV; Suhani, S; Mamatha, H; Sampath, PK (Department of Surgery, UKM Medical Centre, 2013)
Appendectomy is the surgical procedure of removal of appendix. The inflamed or diseased condition of appendix also known as appendicitis is a common occurrence and is a surgical emergency. It commonly occurs due to obstruction of its lumen. The comprehensive information about the trends in the clinical profile of the appendicitis and appendectomy and pattern of its variation with respect to age and gender may help in clinical updates. Hence, this study included a review of case records of all appendectomy patients in a South Indian hospital since the last five years. The data was collected and analysed statistically. A total of 2402 appendectomy operations were found since the last five years (2006-2010). Among them, 1114 cases were males (46%) and 1288 were females (54%).Total number of 1961 (81.6%) cases of appendectomies were performed for the removal of an inflamed appendix and in remaining 441 (18.4%) cases, appendectomy was done along with the other procedures such as hysterectomy, and colectomy. The incidence of appendicitis and appendectomy were higher in females. The survey revealed, higher incidence rate among 16-30 year age group followed by 31-45 and 1-15 years.